Cyanine Phototruncation Enables Spatiotemporal Cell Labeling - Fukushima, Hiroshi; Matikonda, Siddharth S; Usama, Syed Muhammad; Furusawa, Aki; Kato, Takuya; Štacková, Lenka; Klán, Petr; Kobayashi, Hisataka; Schnermann, Martin J (Journal of the American Chemical Society, 2022)
Photoconvertible tracking strategies assess the dynamic migration of cell populations. Here we develop phototruncation-assisted cell tracking (PACT) and apply it to evaluate the migration of immune cells into tumor-draining lymphatics. This method is enabled by a recently discovered cyanine photoconversion reaction that leads to the two-carbon truncation and consequent blue-shift of these commonly used probes. By examining substituent effects on the heptamethine cyanine chromophore, we find that introduction of a single methoxy group increases the yield of the phototruncation reaction in neutral buffer by almost 8-fold. When converted to a membrane-bound cell-tracking variant, this probe can be applied in a series of in vitro and in vivo experiments. These include quantitative, time-dependent measurements of the migration of immune cells from tumors to tumor-draining lymph nodes. Unlike previously reported cellular photoconversion approaches, this method does not require genetic engineering and uses near-infrared (NIR) wavelengths. Overall, PACT provides a straightforward approach to label cell populations with spatiotemporal control.
Keywords: Neoplasms; nádory; lidé; Coloring Agents; Fluorescent Dyes; karbocyaniny; Carbocyanines; barvicí látky; fluorescenční barviva; Humans